The engagement of activating FcgammaRs inhibits primate lentivirus replication in human macrophages - David, Annie (American Association of Immunologists, 2006)
We previously reported that the stimulation of monocyte-derived macrophages (MDM) by plate-bound intravenous immune globulins (IVIg) inhibits HIV-1 replication (Perez-Bercoff et al, J Virol, 2003, 77:4081). Here, we show that IgG immune complexes also suppress HIV-1 replication in MDMs and that activating receptors for the Fc portion of IgG - FcγRI, FcγRIIA and FcγRIII are responsible for the inhibition. MDM stimulation through FcγRs induces activation signals and the secretion of HIV-1 modulatory cytokines, such as M-CSF, TNF-α and MDC. However, none of these cytokines contribute to HIV-1 suppression. HIV-1 entry and post-integration steps of viral replication are not affected, whereas reduced levels of reverse transcription products and of integrated proviruses, as determined by real time PCR analysis, account for the suppression of HIV-1 gene expression in FcγR-activated MDMs. We found that FcγR-dependent activation of MDMs also inhibits the replication of HIV-2, SIVmac and SIVagm, suggesting a common control mechanism for primate immunodeficiency lentiviruses in activated macrophages.